Study of B → DsJ(*)+D̄ (*) decays - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
The study of D*sJ(2317)+ and D sJ(2460)+ meson production in B decays was reported. The decays B+→D(*sJ+̄D(*)0 and B0→D (*)sJ+ D(*̄ was observed. The branching functions for these modes was obtained based on the sample of 122.1 × 106 B̄B pairs collected with the BABAR detector at the PEP-II B factory. An angular analysis of DsJ(2460) + → D+s γ decays was also performed.